Sillons d’usure interproximaux : reproduction expérimentale, analyse et application des résultats aux observations sur la lignée néandertalienne - Linda Bouchneb; Bruno Maureille (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Siffre (1911) was the first to observe, on the left mandibular molars of the La Quina H5 Neandertal, a loss of dental tissues in “gutter” form located at the cemento-enamel junction. By close comparative observations on a living man, he suggested that these grooves were produced by means of a toothpick, for cleaning the food particles accumulated in the interdental space. Since then, several authors have reported interproximal wear grooves in a wide range of fossil hominids, beginning with early Homo. Various etiologies were proposed to explain the existence of this loss of dental substance, but we may consider that at present there is a consensus on toothpick use. Nevertheless no one has yet attempted to reproduce experimentally this type of tooth wear. This study attempts to reproduce grooves at the cement/enamel junction of human premolars using various materials (reindeer bone and antler, calf sinew and wood) with and without abrasive particles. These grooves must be close in appearance to the typical toothpick wear generally described in the literature for fossil teeth. Almost all the materials employed for the experiment, with or without abrasives, produced such grooves. Moreover, they are very close morphologically whatever the nature of the object used as a toothpick. However there is an exception: the flexible material produced marks that we have never seen on Paleolithic fossils. The use of mineral particles appears to increase the speed of wear and to produce deeper scratches.With these experimental results we discuss the interproximal wear grooves observed on teeth of members of Neanderthal lineage. The macro- and microscopic morphology of these experimental grooves is similar to that reported for fossil hominids. Our results thus enable us to suggest that tooth-picks were occasional objects.